2020
DOI: 10.2196/22437
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Postoperative Pain Following Hospital Discharge: Protocol for a Systematic Review

Abstract: This tool is designed to assess the risk of bias in population-based prevalence studies. Please read the additional notes for each item when initially using the tool. Note: If there is insufficient information in the article to permit a judgement for a particular item, please answer No (HIGH RISK) for that particular item. Risk of bias item Criteria for answers (please circle one option) Additional notes and examples

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The lack of patient care in the post-surgical phase results in poorly controlled post-operative pain. Inadequate PO pain management provokes harmful effects on quality of life, contributing to the development of chronic post-surgical pain [ 48 ]. Despite the knowledge regarding the molecular biology and neurology of PO pain, the clinical management of PO pain seems to be unsuccessful [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of patient care in the post-surgical phase results in poorly controlled post-operative pain. Inadequate PO pain management provokes harmful effects on quality of life, contributing to the development of chronic post-surgical pain [ 48 ]. Despite the knowledge regarding the molecular biology and neurology of PO pain, the clinical management of PO pain seems to be unsuccessful [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The review protocol has been previously published, 36 registered in the International Prospective Register of Systematic Reviews (PROSPERO) database (registration number CRD42020194346), and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) checklist. 34 The systematic review is performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines 33 and the Meta-analyses Of Observational Studies in Epidemiology (MOOSE) checklist.…”
Section: Methodsmentioning
confidence: 99%
“…1 A meta-analysis estimated the prevalence of moderate-tosevere postoperative pain 1 to 2 weeks after discharge to be up to 58%. 2 Individuals with poorly managed postoperative pain can experience reduced quality of life, impaired physical function, and reduced sleep. 1 Acute postoperative pain may also transition to chronic pain.…”
Section: Postoperative Pain Managementmentioning
confidence: 99%